Information models for manufacturing workspaces in robotic Projects - Nevliudov, I.; Tsymbal, O.; Bronnikov, A. (ХНУРЕ, 2022)
The subject of research in the article are the workspace models for flexible integrated robotic systems. The goal of the work is in development of information models to represent workspaces for following application in the automated control systems of flexible integrated manufacturing. The article solves the next tasks: to analyze the representation of workspace to decide practical problems of robotic systems of different nature, to consider the development of informational models for representation on workspaces of intelligent control systems of integrated manufacturing, to consider the practical examples of information presentation on workspaces of production systems. Research methods are set theory and predicate theory. The following results were obtained: there were analysed the main features of informational models development to solve robotic tasks of different nature and were pointed the limitations of existing approaches of formal description, the need of integration of workspace models to decision-support systems and systems of graphical and mathematical simulation of integrated systems; the set theory-based model of information representation for problem-solving processes of flexible integrated robotic systems is proposed; the information-logic model of workspace for mobile robot applications, functioning in flexible integrated systems. is developed and contains the list of objects, includes their geometrical dimensions and supplies the preservation of parameters in time and space; information presentation for automated control system of flexible integrated manufacturing, which implements proposed models, is considered. Conclusions: application of models of information type for automated control systems makes to supply logical unification of flexible integrated manufacturing elements, to provide monitoring of states of technological equipment of production systems in space and time and formation of their digital twins, to promote functioning of intelligent decision-support systems for robotic systems of different types, that improves characteristics of production control.
Keywords: information model; workspace; mobile robot; flexible integrated system